A high-resolution record of the last deglaciation in the Sicily Channel based on foraminifera and calcareous nannofossil quantitative distribution - Sprovieri, R; Di Stefano, E; Incarbona. A; Gargano, ME (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
Relative abundance fluctuations in planktic foraminiferal and calcareous nannofossil assemblages are reported on the basis of a high-resolution study of ODP Leg 160 Hole 963D, drilled in the Sicily Strait, near Capo Rossello (southern Sicily). With its 8 m of undisturbed sediments, the core covers the interval from 1.5 to 23 kyr, allowing a 50/100-yr sampling resolution. All the short warm and cold events and sub-events recorded in this time interval in the GRIP Greenland ice core and at several Mediterranean sites were recognized. On this basis, a total number of nine ecozones based on planktic foraminifera and seven ecozones based on calcareous nannofossils were identified. A short interval of climatic amelioration, identified above the base of the Holocene, precedes the segment contemporaneous with the deposition of sapropel S1, which has no lithological expression in the local sedimentary record. This segment has been subdivided into the two warm S1a and S1b phases, separated by a cold intermediate event. A gradual climatic deterioration is recorded above the top of the interval correlated with sapropel S1. It is interrupted by short cold spells, tentatively correlated with similar short duration cold events reported for this interval in the recent literature.